(untitled) (Global Journal of Management and Business Research, 2013)
Green car is not a new word to discuss in India now due to publication of many papers in the area of Environment and in the subject of green marketing. The term green has been discussed a lot by the researchers in many conferences and seminars but it is yet to be practiced by the publishers or by the consumers in India. The green cars have been manufactured in other developed countries and are very well received by the customers. Some of the manufacturers in India have made an attempt of manufacturing green cars for Indian market, anticipating the demand but they are yet to create a niche for themselves and EFC (Environment Friendly Car). Author has made an attempt to understand as to what is the problem with the Indian market for accepting the green car. The problems could be many but the basic problem which has been identified during the study lies with the customers who are aware of what the green car means to them and also on the part of policy makers.